2021
DOI: 10.1007/s10750-020-04494-6
|View full text |Cite
|
Sign up to set email alerts
|

Restoration-mediated alteration induces substantial structural changes, but negligible shifts in functional and phylogenetic diversity of a non-target community: a case study from a soda pan

Abstract: Stream macroinvertebrates, as non-target organisms, may face with either a single or a complex stressor during a restoration treatment. We quantified the structural, phylogenetic, and functional responses to both single (water retention) and complex (water retention and grazing) stressors and analysed how the ecological quality changes, in order to reveal the potential unwanted consequences in a soda pan restoration. Species composition has been restructured and taxonomic diversity decreased significantly as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…However, recent research has shown that PD is less useful for detecting responses of macroinvertebrate communities to stress. Boda et al (2021) found no phylogenetic signal of stream restoration impacts on macroinvertebrate communities using and Arbi et al (2017) observed no differences between species-level indicators (richness, diversity) and measures of PD in macrobenthic communities in response to nutrient pollution.…”
Section: Introductionmentioning
confidence: 87%
“…However, recent research has shown that PD is less useful for detecting responses of macroinvertebrate communities to stress. Boda et al (2021) found no phylogenetic signal of stream restoration impacts on macroinvertebrate communities using and Arbi et al (2017) observed no differences between species-level indicators (richness, diversity) and measures of PD in macrobenthic communities in response to nutrient pollution.…”
Section: Introductionmentioning
confidence: 87%